CONVENTIONAL TURBINOPLASTY AND COBLATION TURBINOPLASTY IN PATIENTS WITH BILATERAL INFERIOR TURBINATE HYPERTROPHY - Sharma, Neha; Deepchand; Gupta, Gaurav; Samor, Vivek; Chhinpa, Govind (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of the study was to compare the efficacy of conventional turbinoplasty and coblation turbinoplasty in patients with bilateral inferior turbinate hypertrophy. Methods: A prospective comparative study was conducted on 60 patients undergoing turbinoplasty at the Department of ENT, Sardar Patel Medical College and PBM Hospital, from July1st, 2021, to June 30th, 2022. About 60 patients were randomly divided into two groups, Group A patients were surgically managed by conventional turbinoplasty, and Group B patients by coblation turbinoplasty. Intraoperatively, the time for each surgery was individually calculated from incision to nasal packing. Follow-up was done at 3 months and at 6 months to assess the post-operative efficacy. Results: The mean age of participants was 36.57±8.01 years (21 years–49 years). On comparing the post-operative mean medial mucosal thickness, and mean airway space achieved in 6 months by both the surgeries, a statistically significant difference was found. The mean duration of surgery for coblation turbinoplasty was 435.50 s or 7.25 min (ranging from 6.17 min to 8.33 min) and 1039.33 s or 17.32 min (ranging from 19.16 min to 15.48 min) for conventional turbinoplasty (p<0.001). Conclusion: Coblation has an upper hand in terms of improvement of patient symptoms and reduction in turbinate size. The only and major deterring factor in the regular usage of coblation is its cost.